Molecular chaperone involvement in chloroplast protein import. - Flores-Pérez, Ú; Jarvis, P (2013)
Chloroplasts are organelles of endosymbiotic origin that perform essential functions in plants. They contain about 3000 different proteins, the vast majority of which are nucleus-encoded, synthesized in precursor form in the cytosol, and transported into the chloroplasts post-translationally. These preproteins are generally imported via envelope complexes termed TOC and TIC (Translocon at the Outer/Inner envelope membrane of Chloroplasts). They must navigate different cellular and organellar compartments (e.g., the cytosol, the outer and inner envelope membranes, the intermembrane space, and the stroma) before arriving at their final destination. It is generally considered that preproteins are imported in a largely unfolded state, and the whole process is energy-dependent. Several chaperones and cochaperones have been found to mediate different stages of chloroplast import, in similar fashion to chaperone involvement in mitochondrial import. Cytosolic factors such as Hsp90, Hsp70 and 14-3-3 may assist preproteins to reach the TOC complex at the chloroplast surface, preventing their aggregation or degradation. Chaperone involvement in the intermembrane space has also been proposed, but remains uncertain. Preprotein translocation is completed at the trans side of the inner membrane by ATP-driven motor complexes. A stromal Hsp100-type chaperone, Hsp93, cooperates with Tic110 and Tic40 in one such motor complex, while stromal Hsp70 is proposed to act in a second, parallel complex. Upon arrival in the stroma, chaperones (e.g., Hsp70, Cpn60, cpSRP43) also contribute to the folding, assembly or onward intraorganellar guidance of the proteins. In this review, we focus on chaperone involvement during preprotein translocation at the chloroplast envelope. This article is part of a Special Issue entitled: Protein Import and Quality Control in Mitochondria and Plastids.